2019
DOI: 10.1111/pace.13585
|View full text |Cite
|
Sign up to set email alerts
|

Vagus nerve stimulation reduces ventricular arrhythmias and increases ventricular electrical stability

Abstract: Background Transcutaneous stimulation of the auricular branch of the vagus nerve (AB‐VNS) is a potentially noninvasive, inexpensive, and safe approach for vagus nerve stimulation that suppresses the induction and duration of atrial fibrillation and reduces sympathetic nerve outflow in healthy humans. Researchers have not determined whether AB‐VNS affects ventricular arrhythmias. Objective To evaluate the antiarrhythmic effects of noninvasive AB‐VNS on ventricular arrhythmias induced by myocardial infarction (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 21 publications
(37 reference statements)
0
15
0
Order By: Relevance
“…Those functional effects can be registered noninvasively in humans and, after additional validation in large animal studies, could be combined into practical bedside systems for calibration and optimization of VNS-based therapies targeting different fibers and organs. For example, the B-fiber PSI could facilitate the optimization of VNS parameters to treat heart failure 19 or cardiac arrhythmias 88 , whereas the C-fiber PSI could act as an index of therapeutic effect in anti-inflammatory application of VNS 18,89 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those functional effects can be registered noninvasively in humans and, after additional validation in large animal studies, could be combined into practical bedside systems for calibration and optimization of VNS-based therapies targeting different fibers and organs. For example, the B-fiber PSI could facilitate the optimization of VNS parameters to treat heart failure 19 or cardiac arrhythmias 88 , whereas the C-fiber PSI could act as an index of therapeutic effect in anti-inflammatory application of VNS 18,89 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the presented PSIs for different fibers, based on non-invasive measured physiological markers, can serve as an indicator of cVNS effectiveness on disease basis, for both at the time of electrode implantation and during follow up visits with health care providers. For example, the B-fiber PSI could facilitate the optimization of stimulation paradigms to treat heart failure 18 or cardiac arrhythmia 73 , whereas the C-fiber PSI could act as an index of therapeutic effect in antiinflammatory application of VNS 17 .…”
Section: Neural and Physiological Selective Index Fiber Recruitment Calibrationmentioning
confidence: 99%
“…Each specimen was trimmed to approximately 1 mm 3 size and directly immersed in precooled 2.5% glutaraldehyde at 4°C overnight (Sbjbio, China, SBJ-0639M). Then, the fixed specimens were subjected to gradient dehydration in an acetone solution, uranium acetate staining, and lead citrate staining as described in our previous study [ 22 ]. The ultrastructure of cardiomyocytes was observed by a JEM-100 CXII TEM (JEOL, Japan, 80 kV), and images were captured at 500x magnification.…”
Section: Methodsmentioning
confidence: 99%
“…Nasi-Er et al also demonstrated that TS reduced the occurrence of spontaneous ventricular arrhythmias in conscious dogs with MI. The potential mechanisms of anti-ventricular arrhythmias may increase ventricular electrical stability and alleviate ventricular interstitial fibrosis (Nasi-Er et al, 2019). In a recent patient study, Yu et al (2017c) found that LL-ta-VNS reduced the incidence of reperfusion-related ventricular arrhythmias during the first 24 h after acute myocardial infarction and improved left ventricular function 5-7 days after reperfusion along with reduced venous cytokine levels.…”
Section: Transcutaneous Auricular Vagus Nerve Stimulation and Cardiovmentioning
confidence: 99%